Adult Suicidality and Therapeutic Engagement: A Systematic Review. - Muscat, Chloé; Verhaegen, Frédéric; Clesse, Christophe (Clinical Psychology & Psychotherapy)
Background: Engagement in mental health care among adults with suicidality remains significantly low, with limited understanding of the factors influencing treatment retention and dropout. Aims: Exploring the factors influencing therapeutic engagement, such as attendance, active participation and completion of therapeutic tasks among adults with suicidality, could offer valuable insights for suicide prevention and management. Methods: This systematic review explored quantitative and qualitative studies examining barriers and/or facilitators to treatment engagement. Four main databases have been explored (PubMed, Embase, PsycInfo and Web of Science). Data were analysed and thematically organised with the help of a content analysis. Results: Eighteen studies focusing on adults experiencing various forms of suicidality, including suicidal ideation, behaviours, plans and attempts, have been included. Engagement is mainly perceived through appointment attendance, active participation or a multidimensional combination of factors. Logistical constraints (service availability, time and money) emerge as the most significant barrier to engagement, followed by stigma, treatment‐related experiences and beliefs and patient perception factors. No consensus between studies can be isolated regarding the impact of social support, severity of suicidal symptoms and psychiatric comorbidities. Trust in mental health professionals and interventions facilitating active patient participation positively influence treatment continuation. Conclusion: This review highlights the need to increase mental health funding to enhance service availability and improve the training of mental health professionals in suicide prevention and management. Developing integrative and empowering interventions fosters an essential climate of trust and hope in therapy that enhances engagement. Future research should prioritise study designs that distinguish between perceived and actual barriers to engagement to develop targeted interventions. Summary: Actively addressing logistical barriers such as cost, time and service availability can support therapeutic engagement in adults experiencing suicidality.Exploring and acknowledging patients' previous treatment experiences, beliefs and experiences of stigma may help reduce barriers to engagement.Therapeutic engagement is enhanced when clinicians foster active patient participation and a sense of empowerment.